Meningkatkan Hasil Belajar PAK Dengan Model PBL Berbantuan Media Interaktif Kancing Gemerincing Tema Manusia Sebagai Pribadi Bagi Peserta Didik Kelas X Fase E SMA Negeri 1 Kudus - Reko Prasojo; Hartutik Hartutik (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
This research aimed to improve the student’s outcames of the X E 7 grade SMA Negeri 1 Kudus year of 2023/2024 in Catholic religious and morals subjects by implementating Problem Based Learning (PBL) model assisted by interactive media kancing gemerincing. This research is a classroom action research that included in two cycle with 2 confluence every cycle. Each cycle consist of planning, acting, observing, and reflecting. The first and second cycle discussed the subject of the unique human beings and gander equality. The subject of this research is the catholic student of X E 7 grade SMA Negeri 1 Kudus year of 2023/2024 which consist of 8 students. The main technique in data collecting used test, and observation, meanwhile the proponent technique used interview and documentation. The result of this research showed that the implementation of Problem Based Learning model assisted by interactive media kancing gemerincing can improve learning outcomes student of X E 7 grade in Catholic religious and morals subjects start from cycle I and cycle II is 81 in cycle I stage increase to be 89 in cycle II. The conclution of this research is the implementation of Problem Based Learning (PBL) model assisted by interactive media kancing gemerincing can improve learning outcomes student of X E 7 grade SMA Negeri 1 Kudus year of 2023/2024.